Who are the early adopters of fuel cell vehicles?. (13th September 2018) - Hardman, Scott; Tal, Gil
Abstract: All new technologies, including automotive technologies, are first purchased by early adopters. These consumers are currently posed with the choice of purchasing a fuel cell vehicle (FCV) or a variety of other alternatively fueled vehicles, including battery electric vehicles (BEVs). For FCVs to be commercially successful they need to carve out their own niche in the automotive market, something which may prove challenging in the face of strong BEV market growth. The results in this paper come from a questionnaire survey of 470 FCV owners and 1550 BEV owners. The paper explores the socio-economic profile, travel patterns, and attitudes of FCV buyers and compares them to the buyers of BEVs. The result suggests that the adopters of BEVs and FCV are similar in gender, level of education, household income, and have similar travel patterns. They have differences in age, ownership of previous alternative fuel vehicles, attitudes towards sustainability, and more FCV owners live in rented homes and apartment buildings. The results of the study suggest that FCVs may appeal to consumers who live in homes where they cannot recharge a BEV or install their own charger. FCVs still have several challenges to overcome, including the lack of hydrogen refueling stations and a lack of FCV models to choose from. Highlights: This paper explores the early adopters of fuel cell vehicles. Fuel cell vehicle adopters are high income, highly educated, and mostly male. They have previously owned other alternative fuel vehicles. More fuel cell vehicle adopters live in apartments or rented homes compared to electric vehicle adopters. Fuel cells may appeal to consumers with range anexity or those who cannot charge a vehicle from home.